The Influence of Leadership Style and Organizational Culture on Performance (Study on 'Indonesia Eximbank' Makassar Regional Office) - Jihad Firman, Muhammad; Kasmita, Maya (Universitas Negeri Makassar, 2023)
This study aims to analyze the influence of leadership style on employee performance and analyze the influence of organizational culture on employee performance at the Indonesian Export Financing Agency (Indonesia Eximbank) Makassar Regional Office. The analytical method used is descriptive analysis method and multiple regression analysis. The results showed that, 1) Leadership style has a positive and significant influence on employee performance at the Indonesia Eximbank Makassar Regional Office. This finding indicates that a leader's leadership style greatly influences the performance of his subordinates, in addition to getting good performance it is also necessary to provide learning to his subordinates, 2) organizational culture has a positive and significant effect on employee performance at the Indonesia Eximbank Makassar Regional Office. This finding indicates that cultural values have become guidelines in making organizational rules, so corporate culture will be able to contribute to organizational performance. This means that if the organizational culture is good, the organizational performance will also be good. Model regression results are best used to predict an increase in the performance of employees is based on secondary data is a model equation (17) for this model produces the coefficient of determination (R) 62% as well as has the ability to explain variations in the rise and fall of dependent variables more than the other models